2014
DOI: 10.1016/j.ympev.2014.03.004
|View full text |Cite
|
Sign up to set email alerts
|

High mountain origin, phylogenetics, evolution, and niche conservatism of arctic lineages in the hemiparasitic genus Pedicularis (Orobanchaceae)

Abstract: The origin of the arctic flora covering the northernmost treeless areas is still poorly understood. Arctic plants may have evolved in situ or immigrated from the adjacent ecosystems. Frequently arctic species have disjunctive distributions between the Arctic and high mountain systems of the temperate zone. This pattern may result from long distance dispersal or from glacial plant migrations and extinctions of intermediate populations. The hemiparasitic genus Pedicularis is represented in the Arctic by c. 28 ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 68 publications
0
37
0
Order By: Relevance
“…long-tubed/ beaked) from generalized ancestors (i.e. short-tubed/ beakless) (Ree, 2005;Eaton et al, 2012;Tkach et al, 2014). This notion has been further supported by (Li, 1951).…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…long-tubed/ beaked) from generalized ancestors (i.e. short-tubed/ beakless) (Ree, 2005;Eaton et al, 2012;Tkach et al, 2014). This notion has been further supported by (Li, 1951).…”
Section: Introductionmentioning
confidence: 76%
“…long‐tubed/beaked) from generalized ancestors (i.e. short‐tubed/beakless) (Ree, ; Eaton et al ., ; Tkach et al ., ). This notion has been further supported by pollination/floral biology studies in Pedicularis , which have found that only short‐tubed, beakless species produce nectar to reward pollinators (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…annual/biennial, insect-pollinated, outcrossing, mid-successional) and has an almost matching distribution range on the QTP with northernmost occurrences in either the Tianshan or the Altay Mts. [43,72,73], the haplotype diversity was slightly higher in P . kansuensis ( H T = 0.882 vs .…”
Section: Discussionmentioning
confidence: 99%
“…S5A-S5C), with particular shifts associated with occurrence in high latitudes. Adaptation to the arctic biome appears to be a recent phenomenon in many plant lineages (Abbott & Brochmann, 2003;Liu et al, 2014), and the lineages that inhabit these areas tend to exhibit phylogenetic niche conservatism (Hawkins et al, 2013;Gebauer et al, 2014;Tkach et al, 2014). Nevertheless, a large number of sedge lineages have acquired the necessary adaptations to survive in Arctic climates, including at least 48 different Carex clades (Hoffmann et al, 2017) and the genera Eriophorum and Trichophorum.…”
Section: Future Research Prioritiesmentioning
confidence: 99%